Evaluation Post PTCA with Cardiac Exercise Stress Test - Fahmi Adam; Hardja Priatna; Hidayani Fazriah (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Coronary Heart Disease (CHD) is an imbalance condition of oxygen supply which causes hypoxic conditions in myocardium, the World Health Organization (WHO) estimates CHD to be the leading cause of death worldwide, with more than 80% occurring in developing countries. In compiling this scientific paper using descriptive methods, research was conducted by collecting data from September 2018 to May 2019 at Tangerang District General Hospital, describing the characteristics and subjects studied and making conclusions. The study began from September to May. Based on the study 2 of 11 patients had a positive exercise test. PTCA measures are able to improve fitness and reduce coronary arteries narrowing, the Load Heart Exercise Test is an appropriate initial method for post-PTCA evaluation, and is quite good in assessing ischemic responses after PTCA actions. Keywords: Coronary Heart Disease, Weight Training Exercise, Percutaneous Transluminal Coronary Intervention. Penyakit Jantung Koroner (PJK) merupakan suatu kondisi ketidak seimbangan suplai oksigen yang menyebabkan kondisi hipoksia pada miokardium, World Health Organization (WHO) mengestimasi PJK menjadi penyebab utama kematian diseluruh dunia ,dengan lebih dari 80% terjadi di negara berkembang. Dalam penelitian ini menggunakan metode deskriptif, penelitian dilakukan dengan pengumpulan data pada di Rumah Sakit Umum Kabupaten Tangerang, menggambarkan karakteristik dan subjek yang diteliti dan membuat kesimpulan. Penelitian dilakukan selama 8 bulan pengambilan data primer di Rumah Sakit Daerah diperoleh 11 pasien memiliki hasil uji latih yang positif. Tindakan PTCA mampu meningkatkan kebugaran dan mengurangi penyempitan pembuluh darah koroner,Uji Latih Jantung Beban adalah metode awal yang tepat untuk evaluasi pasca tindakan PTCA,serta cukup baik dalam menilai respon iskhemik setelah dilakukannya tindakan PTCA. Kata kunci: Penyakit Jantung Koroner, Uji Latih Jantung Beban, Percutaneous Transluminal Coronary Intervention.